Hydrogenated Silicon Carbide Thin Films Prepared with High Deposition Rate by Hot Wire Chemical Vapor Deposition Method. (4th February 2014) - Kamble, M. M.; Waman, V. S.; Mayabadi, A. H.; Ghosh, S. S.; Gabhale, B. B.; Rondiya, S. R.; Rokade, A. V.; Khadtare, S. S.; Sathe, V. G.; Shripathi, T.; Pathan, H. M.; Gosavi, S. W.; et al.
Abstract : Structural, optical, and electrical properties of hydrogenated silicon carbide (SiC:H) films, deposited from silane (SiH4 ) and methane (CH4 ) gas mixture by HW-CVD method, were investigated. Film properties are carefully and systematically studied as function of deposition pressure which is varied between 200 mTorr and 500 mTorr. The deposition rate is found to be reasonably high (9.4 nm/s< r d < 15.54 nm/s). Formation of SiC:H films is confirmed by FTIR, Raman, and XPS analysis. XRD and Raman analysis revealed that with increasing deposition pressure amorphization occurs in SiC:H films. FTIR spectroscopy analysis shows that bond density of C–H decreases while Si–C and Si–H bond densities increase with increasing deposition pressure. Total hydrogen content increases with increasing deposition pressure and was found to be <20 at.%. The absence of band ~1300–1600 cm −1 in the Raman spectra implies negligible C–C bond concentration and formation of nearly stoichiometric SiC:H films. The band gap shows increasing trend with increasing deposition pressure. The high value of Urbach energy suggests increased structural disorder in SiC:H films. Finally, it has been concluded that CH4 can be used as effective carbon source in HW-CVD method to prepare stoichiometric SiC:H films.